Reactions of EFL Learners to an Unfairness Test - Hossein Salarian (Journal of Education and Teacher Training Innovation, 2025)
The matter of bias is more muddled by the problem of obviously differentiating components of culture and instructional background from the language capacities we want to measure. This study investigates the reaction of English as a Foreign Language (EFL) learners to perceived test unfairness, examining the role of social class and gender in test performance. Drawing on fairness theories and using the reading section of the IELTS test, thirty-four intermediate-level learners were initially pretested and grouped according to gender and social class. After exposure to a uniform instructional treatment, participants completed a posttest. For this purpose, both descriptive and inferential statistics were used to compare the results of the groups. In order to make sure that the differences between the groups are not statistically significant, a one-way ANOVA was employed. Results revealed significant disparities in performance linked to social class and gender, suggesting the presence of test unfairness or differential access to the skills required. This study underscores the importance of validating assessment instruments not only in terms of construct validity but also in terms of fairness across sociocultural demographics. There are some theoretical and practical implications involved in this study.